Layered crystals FeIn₂Se₄, In₄Se₃ and heterojunctions on their basis - Kushnir, B.V.; Kovalyuk, Z.D.; Katerynchuk, V.M.; Netyaga, V.V.; Tkachuk, I.G. (Functional Materials, 2017)
A new heterojunction (GP) p-FeIn₂Se₄-n-In₄Se₃ was formed by the mechanical contact of the FeIn₂Se₄ plate with the van der Waals surface of In₄Se₃. Investigation of Volt-Farada's, spectral characteristics and temperature dependences of the VAC of the heterojunction. On the basis of the analysis of electric and photovoltaic characteristics of the GP, a high-quality zone diagram was constructed. The region of spectral photosensitivity of p-FeIn₂Se₄-n-In₄Se₃ GP which is in the range 0.7-1.3 eV, is established.